STRATEGI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) MEMPERTAHANKAN LOYALITAS PELANGGAN - Lukitaningsih, Ambar (Potensio, 2013)
Competition is fierce, and increasingly difficult to maintain customer loyalty. To work around this, companies must recognize the right customers, while managing increasingly complex customer, this is where CRM is needed, the company will be easier to consolidate and analyze customer data, as well as using it as a vehicle to interact intensely. CRM (Customer Relationship Management) is a type of management that specifically discusses the theory regarding the handling of the relationship between the company and its customers with the goal of increasing the companys value in the eyes of its customers. The main goal of CRM is to improve long-term growth and profitability through a better understanding of the habits (behavior) customers. CRM function will allow the company to know and understand the lifetime value of the customer and provide the perfect personal service. The main focus of the most important here is how the company can maintain customers, especially in conducting marketing activities, every effort is made to be able to reach customers as much as possible. The increasing number of market conditions fragmented and new products are arising and increasingly diverse, the greater the chance the customer in getting the products they want and according to the needs. However, now is not how to convey the companys products into the hands of customers, but how companies can provide products in accordance with the wishes and needs of the customer. To be successful CRM program, needs to be done step is to create a customer strategy. It starts with understanding where the customer wanted to build relationships and what is not. Every customer has different needs and likewise they have different values before the company. CRM (Customer Relationship Management) which is a customer relationship management is indispensable in the conduct of a business enterprise or a strategy to serve customers well. CRM role here is not limited to customer satisfaction, but furthermore customers can continue to purchase products and or services that the company can offer, so that with the implementation of this CRM company can serve customers well and retaining customer loyalty.Â Keywords: Â  CRM (Customer Relationship Management), Customer Relationship Management, Customer Loyalty